Predictors of training efficacy during n-back training - Vranić, Andrea (Psihološka obzorja (Ljubljana), 2021)
Numerous studies have investigated the efficacy of various cognitive trainings, with working memory being the most often trained cognitive aspect. In this regard, executive aspects of working memory have received the most attention, with updating training being vastly explored. In this study, we aimed to examine the differential contribution of some individual characteristics to the efficacy of updating training using a well-established n-back training paradigm. More specifically, we examined the contribution of fluid reasoning (gf), and personality (neuroticism, conscientiousness) to training efficacy. Participants (N = 47) took part in a 15-session, dual n-back training, spread over 4 weeks. They were pretested for fluid reasoning (CFT-3), personality (IPIP-100), and performed the initial testing on the OSPAN task. OSPAN was measured in three additional measurement points (after 5th, 10th, 15th session). The data was analyzed within the multilevel modeling approach. Initial hypotheses were partly confirmed, in that: 1) training was efficient in terms of OSPAN score, which grew linearly over time and the trajectory was similar between participants, 2) although the growth was similar for all participants, differences were found in intercepts, and 3) these differences could be partly explained by differences in fluid reasoning, but not with personality traits of conscientiousness and neuroticism.
Keywords: brain training; Cattell's culture fair intelligence test, scale 3 CFT-3; cognitive ability; cognitive processes; cognitive psychology; delovni spomin; International personality item pool-100 IPIP-100; kognitivna psihologija; kognitivni procesi; kognitivni trening; Operational span task OSPAN; osebnostne lastnosti; personality traits; spoznavne sposobnosti; Vprašalnik IPIP-100; working memory